『옥스포드 영한사전』 편찬 작업 및 본 사전의 특징 - 정영국(Jeong Young-kuk) (한국사전학, 2010)
The purpose of this paper is to introduce key features of the newly published Oxford Advanced Learners English-Korean Dictionary (OALEKD, 2009), as well as to touch on some issues which arose while translating Oxford Advanced Learner’s Dictionary (OALD) into Korean. Most of the thorny issues were stemmed from the differences between OALD and existing English-Korean dictionaries in macro- and micro-structures: the division of transitive and intransitive verbs, the sense division of polysemous headwords, and the presentation of guide words for polysemous words. Eventually it was settled on to follow the conventions of OALD in developing OALEKD. This paper also presents key features of OALEKD, particularly focusing on how the dictionary clearly and understandably presents Korean equivalents compared to existing English-Korean dictionaries. KCI Citation Count: 6